The Implikasi Implementasi Kurikulum Merdeka di SD Negeri Sidorejo Lor 3 Salatiga - Satriyana, Vita; Kusumawati, Erna Risfaula (JURNAL SINEKTIK, 2024)
This study describes the implementation of the independence curriculum at SD Negeri Sidorejo Lor 3 Salatiga. The purpose of this research is to find out the implementation of the independent curriculum in elementary schools. This type of research is qualitative research. Data was collected by interviewing teachers. The results of this study indicate that the implementation of the independent curriculum pays attention to the philosophy of Ki Hajar Dewantara. The teacher's duty is to guide the growth and development of students in achieving the highest happiness both as individuals and as members of society. Implementation of an independent curriculum makes teachers flexible in developing learning in the classroom. Teachers are no longer burdened with a variety of solid materials and a lot to be completed in a short time. Students become more enthusiastic and enthusiastic in learning activities. The potential possessed by students becomes increasingly visible and developing. The implementation of this independent curriculum is supported by various stakeholders, so that it can run well and smoothly without any obstacles. Guardians of students also support and are actively involved in projects to strengthen the profile of Pancasila students.